Religion in New Media: Anti-Dating Movement in Instagram - Puteri, Perdana Aysha (Al-Adyan: Journal of Religious Studies, 2020)
The young marriage movement on Instagram is able to become a new ideology and identity for young Muslims in Indonesia. This research aims to show how the work of new media affects and blurs the barriers between the private and the public. The youth marriage movement promoted through new media can make someone simply let strangers influence their views on private matters and open up spaces to share views on these matters. To explain this, this study examines how written and visual narratives are conveyed. This research also examines how the pros and cons emerge in the social context of the Indonesian Muslim community, particularly regarding the marriage issues. To build an argument, the study analyzed some content and interactions between users in online publications on the Instagram accounts @gerakannikahmuda and @indonesiatanpapacaran. This study also analyzes counter responses conveyed through articles in several online media. This research uses content analysis which is not limited to these two accounts, but also the debates that arise from these ideologies and movements. In sum, this study confirms that in the era of new media, a person has options that are open, broad and very easy to influence himself to become a new grip, ideology and identity, only with digital activities.Gerakan nikah muda di Instagram mampu menjadi ideologi dan identitas baru bagi pemuda Muslim di Indonesia. Penelitian ini bertujuan untuk menunjukkan bagaimana peran media baru mempengaruhi dan mengaburkan batas antara pribadi dan publik. Gerakan pernikahan muda yang dipromosikan melalui media baru dapat membuat seseorang membiarkan orang lain mempengaruhi pandangannya tentang masalah pribadi dan membuka ruang untuk berbagi pandangan tentang masalah tersebut. Untuk menjelaskan hal tersebut, penelitian ini mengkaji bagaimana narasi tertulis dan visual disampaikan.  Penelitian ini juga mengkaji bagaimana pro dan kontra yang muncul dalam konteks sosial masyarakat Muslim di Indonesia, khususnya terkait masalah perkawinan.  Untuk membangun argumen, kajian ini menganalisis beberapa konten dan interaksi antar pengguna dalam publikasi online di akun Instagram @gerakannikahmuda dan @indonesiatanpapacaran.  Studi ini juga menganalisis tanggapan balasan yang disampaikan melalui artikel di beberapa media online.  Penelitian ini menggunakan analisis isi yang tidak terbatas pada dua akun tersebut, tetapi juga perdebatan yang muncul dari ideologi dan gerakan tersebut. Singkatnya, kajian ini menegaskan bahwa di era media baru, seseorang memiliki pilihan yang terbuka, luas dan sangat mudah mempengaruhi dirinya untuk menjadi pegangan, ideologi dan identitas baru, hanya dengan aktivitas digital.